2018
DOI: 10.1002/jmri.26339
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between an abbreviated and full MRI protocol for detecting additional disease when doing breast cancer staging

Abstract: Background Previous studies have shown that abbreviated magnetic resonance imaging (aMRI) compares well to full‐protocol MRI (fpMRI) in breast cancer (BC) screening, with the potential advantage of a less costly and complex examination. To our knowledge, the role for aMRI in staging BC has been poorly investigated, especially in assessing additional disease (ie, additional lesions compared to the index one prompting the examination). Purpose To compare aMRI and fpMRI in detecting additional disease in BC stagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In two others, the evaluation of recurrency was addressed [52,60]. Two of the articles evaluating the use of ABB-MRI for the extent of the disease assessing [57,61], and the other one for detecting additional lesions in confirmed breast cancer patients [74]. A total of 15, 680 breast MRI studies were evaluated in the includes studies, 4934 of which were acquired prospectively.…”
Section: Study Purpose and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In two others, the evaluation of recurrency was addressed [52,60]. Two of the articles evaluating the use of ABB-MRI for the extent of the disease assessing [57,61], and the other one for detecting additional lesions in confirmed breast cancer patients [74]. A total of 15, 680 breast MRI studies were evaluated in the includes studies, 4934 of which were acquired prospectively.…”
Section: Study Purpose and Populationmentioning
confidence: 99%
“…Six aimed to evaluate the feasibility of using abbreviated protocols to screening high risk women [35,46,59,39,53,55]; and 7 others, to women with a personal or family history of breast cancer [71,36,43,37,58,44,60]. Additionally, 3 studies established as inclusion criteria to present lesions previously identified by another imaging modality [69,70,67]; and the other 4, focused on pathologically proven breast cancer studies [74,57,68,61].…”
Section: Study Purpose and Populationmentioning
confidence: 99%
“…This knowledge may have influenced the readers’ assessment. Our study is not unique in this regard, and approximately half of the published studies on this topic have a cancer-enriched cohort ( 7 , 10 , 11 , 13 15 , 17 19 , 29 31 ). There were relatively few lesions with benign histology, most likely because of exclusion of all women with prior breast surgery.…”
Section: Discussionmentioning
confidence: 98%
“…So, the abbreviated protocol could be reliably applied in identifying disease extension. Another study by Girometti et al, compared the abbreviated and the standard protocol for additional diseases during breast cancer staging in 87 patients with 89 biopsy-proven main lesions [22] . The authors showed that abbreviated MRI was comparable to standard MRI in staging additional breast cancers (multifocal, multicentric, and contralateral) which further indicates the imperative role of the shortened breast MRI protocol in the future clinical practice.…”
Section: Discussionmentioning
confidence: 99%